ANALISIS KEPUASAN NASABAH TERHADAP DIGITAL SAVING PADA APLIKASI BRIMO MENGGUNAKAN METODE PIECES FRAMEWORK - Yana Iqbal Maulana; Anshori Dwi Putra; Wiwiek Widyastuty; Arief Rusman; Jefi Jefi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
User satisfaction is a feeling that arises from comparing the performance of a service with the expectations held by its users. In the context of the BRImo application, user satisfaction can be assessed through the efficiency of opening a savings account digitally. However, mobile banking services still face several challenges, including connection disruptions and transaction failures caused by system errors, which may reduce customer trust. This study employs the PIECES Framework, consisting of six variables: Performance, Information and Data, Economics, Control and Security, Efficiency, and Service, to evaluate the system comprehensively and systematically. This method enables the identification of strengths and areas requiring improvement to ensure the system effectively meets user needs. The results indicate average scores of 4.7 for Performance, 4.411 for Information, 3.658 for Economics, 4.6 for Control and Security, 4.416 for Efficiency, and 4.272 for Service. Based on these findings, the level of user satisfaction with the BRImo application falls within the satisfied category, indicating that the application provides high-quality services and is capable of meeting or even exceeding user expectations in supporting digital banking activities.